Hospital information system modeling - Kaghazchi, Hamid Reza (2008)
A hospital consists of different organizational units with specified activities. Conduction of an effective communication throughout this heterogeneous organization is very intensive. Developing a comprehensive model is essential for information managers to ensure about the quality of information systems and understanding the communication within the hospital. So far, many various models have been developed to support the information managers but each one of them present only one aspect of hospital information system. This study is set out to consider the different suggested models for hospital information system and then to look at their advantages and disadvantages in comparison with other models. Pusat Kesihatan UTM has been chosen as a particular small-medium hospital to explore the problems in the heterogeneity of hospital information and to experiment the selected hospital information system model. This is where this project comes in; to study the current information system architecture and the quality of information system at UTM Clinic and to propose a comprehensive hospital information system model to support information system managers who are involved within the clinic. Qualitative method is used to get needed information and study the current situation of information system at the clinic. Internal interview was carried out with the director and information manager of Pusat Kesihatan UTM to understand the weaknesses of the current system within the clinic and also to recognize the expectations of top managers of the clinic. Certain common standards such as reference models were used to identify the existing gaps within the current system and suggest an efficient strategy towards implementation. Through the analysis of different models, this study came up with a meta model called 3LGM which present three aspects of hospital information system that include enterprise functions, logical tools, and physical tools and the relation between each layer with other layers. It is hoped that this project can provide benefits to the Pusat Kesihatan UTM.